Creating awareness on bullying and cyberbullying among young people: Validating the effectiveness and design of the serious game Conectado. (July 2021) - Calvo-Morata, Antonio; Alonso-Fernández, Cristina; Freire, Manuel; Martínez-Ortiz, Iván; Fernández-Manjón, Baltasar
Highlights: Serious games can help to prevent and address bullying and cyberbullying. We combine questionnaires and game analytics to validate a serious game. Use of in-game player analytics improves validation. We found gender differences in time and game choices during the experiments. Abstract: Serious games have proven to be educational tools with numerous positive effects, capable of promoting learning, changing behavior, or improving training and skills development, among other effects. Serious games can also be applied to address and prevent social problems. This study describes the experiments and analyses we have carried out to test the effectiveness of Conectado, a serious game created to prevent bullying and cyberbullying in schools by increasing awareness of the problem in players. We have used the results from these experiments to answer different research questions regarding the game's acceptance and effectiveness, validating several characteristics of the game design. We have also studied the influence of players' characteristics on the effect of the game, as well as the relationship between the in-game behaviors of players and their degree of awareness. We have verified a positive effect of the game in terms of an increase of awareness regarding bullying and cyberbullying for all target users, and have provided further insight into how this increase is related to different players' characteristics and behaviors.